2018
DOI: 10.1088/1742-6596/1049/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Lighting system design according to different standards in office building: A technical and economic evaluations

Abstract: Abstract. Lighting system is an important sub-system in office buildings. A good design can contribute energy saving and visual comfort to occupants. This paper presents a comparison of lighting system design according to different standards: European Standard EN12464-1 and Malaysian Standard MS1525 in terms of average illuminance level and illuminance uniformity. In the design, the illuminance measurement is according to the Illuminating Engineering Society of North America (IESNA) and the European Standard E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…During experimentation it is found that once again the LED tube lights give the highest efficacy among all tube lights t the tune of 84 to 118 lumens / watt as compared to just 26 and 30 lm/W by earlier technology fluorescent lamps. The specifications from the various manufacturers ie s theoretical values and compared with the values that observed during testing of the lighting fixtures, it is found that the actual vales differ from the rated values as shown in above tables (2)(3)(4)(5)(6) and graphs (3)(4)(5).…”
Section: Fig I Experimental Setup Of Various Type Of Illumination Systemmentioning
confidence: 95%
“…During experimentation it is found that once again the LED tube lights give the highest efficacy among all tube lights t the tune of 84 to 118 lumens / watt as compared to just 26 and 30 lm/W by earlier technology fluorescent lamps. The specifications from the various manufacturers ie s theoretical values and compared with the values that observed during testing of the lighting fixtures, it is found that the actual vales differ from the rated values as shown in above tables (2)(3)(4)(5)(6) and graphs (3)(4)(5).…”
Section: Fig I Experimental Setup Of Various Type Of Illumination Systemmentioning
confidence: 95%
“…In [8], they mentioned that the factors affecting are sky conditions and weather, numbers and location of the sensors, type of use and occupancy. Apart from the abovementioned, the design illuminance level is also one of the main factors of these as results finding in [2,47,48].…”
Section: Factors Affecting the Performance Of The Strategiesmentioning
confidence: 99%
“…Based on this fact, the energy consumption needs to be reduced for economic and environmental benefits. There are several strategies can be considered: converting low energy efficient lamp technologies to high energy efficient lamp technologies, such as light emitting diode (LED) [2], occupancybased control and daylight-based control [3] and scheduling-based control [4]. In literature, LED lamp technology has a prominent energy efficient lamp among other lamp technologies due to its special characteristic: high color temperature and efficacy as well as less power consumption [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Only ESLs will be used in future smart lighting systems, then there is an increasing interest in studying the new devices in their large applications. The optimal lighting system design in different indoor applications of ESLs have been investigated by considering several constraints and objectives: cost saving, energy efficiency and management, functional suitability, system integration, people satisfaction, and quality of lighting [31][32][33][34][35][36][37][38]. Moreover, it is important to point out the different innovative solutions in the modern agriculture consist on the development of facilities LED lighting technology.…”
Section: Related Workmentioning
confidence: 99%